Gaps in Hepatitis A and Hepatitis B Vaccination Among Hepatitis C Antibody–Positive Individuals Experiencing Homelessness. (7th April 2022) - Partida, Diana; Powell, Jesse; Gonzalez, Daniel; Khalili, Mandana
Abstract: Vaccination for both hepatitis A (HAV) and hepatitis B (HBV) is recommended in hepatitis C infection (HCV). Among HCV antibody–positive persons experiencing homelessness, we identified high rates of HAV (34%) and HBV vaccine (35%) eligibility, highlighting critical gaps in HCV preventative services. Following education, 54% and 72% underwent HAV and HBV vaccination, respectively.